Strategi Guru Pendidikan Agama Islam dalam Pembinaan Akhlak untuk Mengurangi Perilaku Kenakalan pada Peserta Didik - Muhamad Khoirul Arifin; Didik Wahyudi; Baharudin Baharudin (Universitas Muhammadiyah Mataram, 2026)
This study aims to describe the strategies employed by Islamic Religious Education teachers in fostering students' moral character to reduce delinquent behavior among eleventh-grade students at SMA Minhajuttulab Labuhan Ratu Baru, East Lampung. This research employed a descriptive qualitative approach. Data were collected through observations of 25 eleventh-grade students, interviews with four informants consisting of a PAI teacher, a homeroom teacher, a Guidance and Counseling teacher, and one eleventh-grade student, as well as documentation. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing, supported by source and technique triangulation. The findings revealed that the PAI teacher implemented humanistic, collaborative, and religious approaches through the habituation of religious activities and moral development. These strategies were supported by a religious school environment but were hindered by peer influence, digital media, and the low level of awareness among some students.